2016
DOI: 10.1186/s12882-016-0241-7
|View full text |Cite
|
Sign up to set email alerts
|

Acthar gel in the treatment of nephrotic syndrome: a multicenter retrospective case series

Abstract: BackgroundCurrent first-line anti-proteinuric treatments for nephrotic syndrome (NS) do not produce an effective response in all patients and are not tolerated by some patients. Additional effective and tolerable treatment options in NS are strongly needed. This retrospective case series is the largest to date to examine Acthar gel (adrenocorticotropic hormone, ACTH) in patients with varied-etiology NS.MethodsThis multicenter retrospective case series included adult patients with NS (N = 44) treated with Actha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 23 publications
(37 reference statements)
3
68
2
Order By: Relevance
“…The negative trial findings contrast with recent case series that have suggested that ACTH is effective in reducing proteinuria in adults with nephrotic syndrome (18,(23)(24)(25)(26). Our trial differs from adult experiences in several important ways.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The negative trial findings contrast with recent case series that have suggested that ACTH is effective in reducing proteinuria in adults with nephrotic syndrome (18,(23)(24)(25)(26). Our trial differs from adult experiences in several important ways.…”
Section: Discussioncontrasting
confidence: 92%
“…However, by the 1960s, ACTH was replaced by oral prednisone for its ease of administration and the belief that ACTH acts via stimulation of corticosteroid production (8,13,14). More recently, several case series of patients with steroid-and multidrug-resistant nephrotic syndrome reported ACTH to be efficacious in inducing and sustaining disease remission and improving GFR, which suggests that ACTH has effects beyond steroidogenesis (13,(15)(16)(17)(18). In addition, one randomized trial demonstrated similar efficacy when comparing ACTH with methylprednisolone and a cytotoxic agent in membranous nephropathy, renewing interest in ACTH for nephrotic syndrome treatment (19).…”
Section: Introductionmentioning
confidence: 99%
“…Achtar gel is unusual in that it was approved in the 1950s by the US Food and Drug Administration for nephrotic syndrome under criteria that were less stringent than required today. Small case series suggest limited efficacy of Acthar in some individuals with FSGS (117,118) as has been reviewed (119); a randomized, controlled trial is in progress. Galactose, proposed as therapy for recurrent FSGS, has been shown to lack efficacy in steroid-resistant primary FSGS in children (120).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Currently Acthar has re-emerged and is the most promising treatment option for proteinuria in patients with nephrotic syndrome, patients for treatment-resistant to first-line therapies, patients unable to tolerate first-line therapies and patients with advanced disease [7][8][9]. Acthar is a repository corticotrophin which binds to the Melanocortin 1 receptors (MC1Rs) and potentially providing a different way to impact various cells including podocytes [10,11], thus help regulate protein filtration by reducing podocyte foot process effacement and podocyte loss [7].…”
Section: Introductionmentioning
confidence: 99%
“…Acthar is a repository corticotrophin which binds to the Melanocortin 1 receptors (MC1Rs) and potentially providing a different way to impact various cells including podocytes [10,11], thus help regulate protein filtration by reducing podocyte foot process effacement and podocyte loss [7]. The patients treated with Acthar got full or partial remission for long term effect [8]. Here, we report the case of a patient suffering from proteinuria due to a mixed nephritic-nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%